a) -140
b) -220
c) -86
d) -50
Let f(x)=−3x^(2)−4.
Let g(x)=4x−2.
Find the following:
(a) f(8)+g(8)=
(b) f(5)⋅g(5)=
(c) f(g(8))=
(d) g(f(6))=
2 answers
AAAaannndd the bot gets it wrong yet again!
f(x) = −3x^2−4
g(x) = 4x−2
f(g) = -3g^2-4 = -3(4x-2)^2 - 4
so f(g(8)) = -3(4*8-2)^2 - 4 = -2704
Do the others in like wise. I assume the bot messed them up as well.
Come back with your work if you get stuck
f(x) = −3x^2−4
g(x) = 4x−2
f(g) = -3g^2-4 = -3(4x-2)^2 - 4
so f(g(8)) = -3(4*8-2)^2 - 4 = -2704
Do the others in like wise. I assume the bot messed them up as well.
Come back with your work if you get stuck